Habitat restoration and native grass conservation: a case study of switchgrass (Panicum virgatum). Issue 3 (21st September 2017) - Chang, Hsiaochi; Alexander, Helen M.; Mutegi, Evans; Snow, Allison A.
Abstract : Switchgrass ( Panicum virgatum ) has been planted extensively for habitat restoration across the United States, such as with the Conservation Reserve Program (CRP). However, genetic profiles of these populations have never been studied nor compared with those of remnant prairies or cultivars. In this study, we sampled 16 CRP and 17 prairie populations across eastern Kansas. We assessed ploidy levels of all populations and compared genetic diversity and structure of 10 prairies, 10 CRP areas, and 5 standard cultivars, using nine simple sequence repeat (SSR) DNA markers. All CRP and prairie populations were octaploid (8x), except two prairies with both hexaploid (6x) and octaploid (8x) individuals. Based on the results of SSR analyses, there were no significant differences between CRP and prairie populations in genetic diversity, and 94% of total variation was partitioned within populations. Similarities among prairie and CRP populations were also observed in Bayesian clustering algorithms and principal coordinate analysis, suggesting that they had similar genetic compositions. In addition, positive spatial autocorrelations were detected up to 42 and 46 km among prairie and among CRP populations, respectively. To conclude, the CRP and prairie populations shared similar genetic profiles. However, remnant prairies still harbored unique genotypes and a high level of genetic diversity, highlighting the importance of seed sources for restoration efforts, that is using local wild seeds or cultivars from the same geographical region. A popular tetraploid (4x) cultivar known as "Kanlow" was genetically distinct from the prairie populations and therefore is not recommended for habitat restoration in this region.